Emotional Dynamics and Self-Identity of Boys in the Face of Losing Father Figures - Nabila Putri; Sri Nurhayati Selian (Program Studi Bimbingan dan Konseling Islam IAIN Palu, 2025)
This research aims to understand in depth the dynamics of emotions and the formation of self-identity in boys who experience the loss of a father figure. The approach used was qualitative with phenomenological methods, through in-depth interviews with 3 male participants aged 19–21 years who lost their father due to various factors, such as divorce, death or neglect. The results showed that losing the father figure gave rise to negative emotions such as sadness, longing and loneliness, but over time the participants were able to manage these emotions through adaptive coping mechanisms such as prayer, self-reflection and social support from the mother, friends and the surrounding environment. This process plays a role in forming self-identity as an independent, responsible and highly empathetic man. The experience of loss actually becomes a turning point in strengthening moral values and emotional maturity, indicating positive growth after loss (post-traumatic growth). These findings confirm the importance of emotional support and a positive social environment for boys who have lost their father figure, in order to enable them to develop healthily from both psychological and social aspects.